What Makes a University? Conceptual Determinants from a Contextual Perspective - Arafat, Md. Yeasir; Md. Sobuj Mia; Md. Amirul Islam; Md. Radone Islam Ridoy; Fahmida , Fahmida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The term “university” carries a long intellectual, historical, and cultural legacy, yet the criteria for recognizing an institution as a university remain fluid and context-dependent. This study seeks to explore how an institution comes to be regarded as a university by examining the conceptual, historical, structural, and societal determinants that shape this recognition. Drawing on a qualitative and interpretive approach, the paper analyzes classical understandings of the university, traces the evolution of the term, and examines contemporary expectations surrounding higher education institutions. The discussion highlights that the idea of a university extends beyond legal designation; it is rooted in scholarly traditions, academic autonomy, breadth of knowledge, research culture, institutional mission, globalization, and societal perception. The findings reveal that while regulatory standards provide formal recognition, the deeper legitimacy of a university emerges from its ability to cultivate knowledge, uphold intellectual freedom, and contribute meaningfully to society. This conceptual inquiry therefore offers a contextual framework for understanding how institutions attain the identity of a university, and why this identity continues to evolve in response to educational, cultural, and global transformations.